Pollen foraging preference based on floral resource distance in Tetragonula biroi - NURAENI, SITTI; TIWI, ANDI AMINA; PRASTIYO, ANDI (Asian Journal of Agriculture, 2025)
Abstract. Nuraeni S, Tiwi AA, Prastiyo A. 2025. Pollen foraging preference based on floral resource distance in Tetragonula biroi. Asian J Agric 9: 423-432. The stingless bee Tetragonula biroi plays a vital role as a pollinator and depends primarily on pollen and nectar for nutrition. Understanding its foraging behavior is essential for optimizing floral resource management in meliponiculture systems. This study investigates the foraging preferences of T. biroi based on the distance of floral resources in Awani Bee Garden, Makassar, South Sulawesi, Indonesia. Pollen identification was conducted using light microscopy on bee bread samples collected from three hives, and the spatial distribution of flowering plants around the hives was documented. This research was conducted from November 2023 to February 2025, using descriptive analysis of pollen types and plant distance from the hive. A Spearman’s correlation analysis was also conducted to examine the relationship between the distance of floral sources and the percentage of pollen collected. Foraging preference was operationally defined as the percentage of pollen collected from each plant species relative to its distance from the hive. Results revealed that T. biroi collected pollen from 18 plant species located at distances ranging from 2 to 498 m. The most dominant pollen sources were Clerodendrum paniculatum (16.87%), Macaranga tanarius (15.20%), and Carica papaya (13.97%). Over 70% of the total pollen came from plant species located within 10 m of the hive, such as Capsicum annuum (2 m, 6.93%), Mangifera indica (2 m, 7.49%). However, the bees also utilized distant sources such as Turnera subulata (485 m, 0.56%) and Antigonon leptopus (498 m, 2.12%), demonstrating flexible foraging behavior within their ecological range. Spearman's correlation showed a weak negative relationship between plant distance and pollen percentage (? = -0.387) with p>0.05, indicating that the preference for nearby floral sources was not statistically significant but ecologically observable. These findings suggest that while proximity plays a role in foraging, T. biroi exhibits adaptable behavior based on resource distribution.